Clonal replacement and heterogeneity in breast tumors treated with neoadjuvant HER2-targeted therapy - Jennifer L. Caswell-Jin (Nature Portfolio, 2019)
When examining the evolution of treatment resistance in breast cancer, perceived genomic changes may be due to clonal evolution or heterogeneous tumors. Here, the authors show that apparent clonal change can in fact be due to pre-treatment heterogeneity, and samples from at least two regions are necessary to detect treatment-induced clonal shifts